Efficiency of commercial banks in Pakistan: application of SFA and value added approach - Afza, Talat; Ali Asghar, Muhammad Jam-e-Kausar (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the study is to examine the efficiency of commercial banks in Pakistan over the period of 2005 to 2010. This study has used two-step process for this analysis. Firstly, we applied the Stochastic Frontier Approach (SFA) to examine the overall efficiency trend of commercial banks. We used the value added approach for the selection of input and output variables for the first time in Pakistan to examine the cost and profit efficiency of commercial banks. It is suggested that in developing countries with low savings of people, higher cost of deposits and high competition to attract larger number of deposits, it is inappropriate to place deposits as outputs instead of inputs by following an intermediation approach. The results suggested that the profit and cost efficiency of banks is slightly improved over the study period. Secondly, the association of various firm specific variables along with financial reforms and financial crises with the efficiency of the commercial banks is investigated. Tobit analysis results indicated that variables like size, profitability, equity and an increase in the minimum capital requirement are found to be positively related whereas the provision for advances (loans) is found to be negatively related with the efficiency of commercial banks in Pakistan. It can be concluded that the large size, higher solvency and increase in minimum capital requirement has helped the commercial banks to operate at an optimum level
Argumenta Oeconomica, 2017, Nr 1 (38), s. 195-220
Keywords: commercial banks; efficiency; Stochastic Frontier Approach; Value Added Approach; Minimum Capital Requirement